ALAT MUSIK PERKUSI DI ASIA TENGGARA (SEBUAH KAJIAN ARKEOMUSIKOLOGI) - Peter Ferdinandus (Berkala Arkeologi, 1995)
Research on music in archeology has so far been less desirable, because of its abstract nature. Music relics are often a question whether visual data such as reliefs can be assumed on how it sound. As a result, music data is not given enough attention. For example, the discovery of the bronze nakara in the shape of a drum in Southeast Asia at the beginning of the 19th century AD. The attention of European scholars at that time was only on form, decoration and function.